A State of Alcohol Hangover Impedes Everyday Prospective Memory - Heffernan, Thomas (Frontiers in Human Neuroscience, 2018)
The aim of the current study was to investigate what impact a state of alcohol hangover (AH) has upon everyday prospective memory (PM; memory for future events/intentions). Previous research has shown that the AH has a detrimental effect upon cognitive abilities, including memory and attentional deficits. No published research articles to date have focused upon what impact AH might have upon everyday memory, of which PM is a good example. The current study compared an AH group (AHG) with a non-hangover group (NHG) on PM. Since other drug use, anxiety and depression can affect PM independent of the AH, these covariates were controlled for in the study. Fifty-eight young adults studying at university participated in this between-subjects design study-25 in the AHG and 33 in the NHG. The Prospective Remembering Video Procedure (PRVP) measured PM. The Acute Hangover Rating Scale confirmed a state of AH and a Digital Breath Analyzer Test measured their BAC. The Hospital Anxiety and Depression Scale gauged levels of anxiety and depression and a Recreational Drug Use Questionnaire (RDUQ) measured alcohol and other drug use. Anyone who reported having used an illicit substance (e.g., cannabis, ecstasy) or who smoked, were excluded from the study. After controlling for age, alcohol units per week, years spent drinking alcohol, anxiety and depression scores, a one-way analysis of covariance (ANCOVA) revealed that the AHG (mean = 5.16) recalled significantly fewer items on the PRVP than the NHG (mean = 7.51)—F(1,52) = 5.69, p < 0.05. Overall, it appeared that a state of AH significantly impaired PM, which was not attributable to age, alcohol use, or anxiety or depression indices. Given the importance of PM to everyday activities, such as remembering to keep appointments or to take an important medication on time, this finding may have farther-reaching implications. These findings should also be used to educate young adults and health professionals dealing with the consequences with regards the dangers of alcohol misuse.